Developmental dynamics between mathematical performance, task motivation, and teachers' goals during the transition to primary school. - Aunola, Kaisa; Leskinen, Esko; Nurmi, Jari-Erik (The British journal of educational psychology, 2006)
It has been suggested that children's learning motivation and interest in a particular subject play an important role in their school performance, particularly in mathematics. However, few cross-lagged longitudinal studies have been carried out to investigate the prospective relationships between academic achievement and task motivation. Moreover, the role that the classroom context plays in this development is largely unknown.
Keywords: Finlande; contenus de l'éducation; mathématiques; motivation